Animal Farming and Entrepreneurship Ventures - Ali Farzpourmachiani (Journal of Biotropical Research and Nature Technology, 2025)
Animal farming is transforming from subsistence-oriented conventional practices to wards market-driven entrepreneurial enterprises. The current review integrates peer-reviewed studies and experiential knowledge on economic factors, business models, uptake of digital technology, finance, gender, sustainability, and policy impacts encapsulating livestock entrepreneurship in various income contexts. Based on global and national data, it offers practical tools such as business model charts, unit economics charts, technology solutions, finance options, and risk management techniques available to entrepreneurs, cooperatives, investors, and policymakers. Some of the most important findings are: (i) profitability depends on feed quality, animal productivity, market access, and business skills; (ii) the application of digital technologies accelerates herd management and disease surveillance; (iii) there are still financing gaps despite value-chain financial products under development; (iv) gender participation and benefits are shaped by inclusive business operations; and (v) considerations for sustainability increasingly connect climate change, animal welfare, antimicrobial resistance, and market advantage. A forward agenda is outlined for developing "enterprise-ready" animal agriculture that combines technical efficiency, entrepreneurial capability, risk finance, and open sustainability.